Perbandingan Hasil Pengukuran Volume Overburden Dengan Unmanned Aerial Vehicle Dan Total Station - Harjuni Hasan; Reonaldo Purba; Aprisal Aprisal (Universitas Mulawarman, 2026)
Current volume measurement and calculation with the total station still utilize human plotting, in which surveyors are required to measure plots to obtain coordinate data. This process is time-consuming and costlier. However, technological advancement has allowed the use of unmanned aerial vehicles, or drones, to measure the overburden volume. More than nine images’ overlappings were identified based on the color, and the entire block was in the blue color, meaning that all blocks overlapped in more than nine aerial images. The use of seven GCPs showed horizontal and vertical Root mean square error (RMSE) values of 0.08 and 0.16 meter, respectively. The value was lower than the use of 5 and 3 GCPs, indicating that more GCPs may lead to better RMSE values and affect the Circular (CE90) and linear error (LE90) values. Values obtained using seven GCPs meet the class-2 standard of a 1:1000 map with a contour interval of 0.14. Meanwhile, using 3 GCPs meets only the class-2 standard of a 1:25000 map with a 10-meter contour interval, and using 5 GCPs meets the class-2 standard of a 1:1000 map with a 0.4-meter contour interval. The calculated overburden volume based on aerial photos with seven GCPs in blocks I, II, and III was 47.22.74 BCM, 8251.22 BCM, and 7089.49 BCM, respectively. Meanwhile, that of the total station for the same blocks was 45250.00 BCM, 8127.65 BCM, and 6827 BCM, respectively.